The book of lost friends [large type] : a novel - Wingate, Lisa (Random House Large Print, 2020)
"Louisiana, 1875: In the tumultuous aftermath of Reconstruction, three young women set off as unwilling companions on a perilous quest: Lavinia, the pampered heir to a now-destitute plantation; Juneau Jane, her illegitimate free-born Creole half-sister; and Hannie, Lavinia's former slave. Each carries private wounds and powerful secrets as they head for Texas, following dangerous roads rife with ruthless vigilantes and soldiers still fighting a war lost a decade before. For Lavinia and Juneau Jane, the journey is one of inheritance and financial desperation, but for Hannie, torn from her mother and eight siblings before slavery's end, the pilgrimage westward reignites an agonizing question: Could her long-lost family still be out there? Beyond the swamps lie the seemingly limitless frontiers of Texas and, improbably, hope. Louisiana, 1987: For first-year teacher Benedetta Silva, a subsidized job at a poor rural school seems like the ticket to canceling her hefty student debt--until she lands in a tiny, out-of-step Mississippi River town. Augustine, Louisiana, seems suspicious of new ideas and new people, and Benny can scarcely comprehend the lives of her poverty-stricken students. But amid the gnarled live oaks and run-down plantation homes lies the century-old history of three young women, a long-ago journey, and a hidden book that could change everything."--